The Right to Dignity and Consensus in the Psychiatric Health Treatment - Marinič, Milena (International Journal of Medical and Health Sciences Research, 2017)
Theoretical frameworks: Health workers in practice obtain the informed consent of the patient where there is an invasion of privacy. Health data are processed without consent, health treatment is carried out without informed consent, and is taken to the patient the possibility of an appeal, does not receive information about what to do and where to seek help, if necessary. Methods: Based on the long-term observation of conduct of healthcare workers, the analysis of legal acts and synthesis of statutory provisions for informed consent based arguments. Results Health workers against health interventions with greater impact on privacy and the integrity of the body does not obtain informed consent, offer a preprinted form. The patient is given an explanation focus, which is the duty doctor. Interpretation duty is not subject recording in health documentation which makes it impossible to trace back. Discussions Health professionals legislature requires compliance with legal rules, education in terms of knowledge of the law, it does not reach a satisfactory level. Health workers do not know the laws, and the patient's rights not exercised. In order to ensure the legal documentation is necessary to inform all health professionals with the laws and knowledge documentation.